Pragmática del español : contexto, uso y variación - Félix-Brasdefer, J. César (Routledge introductions to Spanish language and linguistics, 2019)
Pragmática del español introduces the central topics in pragmatics and discourse from a sociolinguistic perspective. Pragmatic variation is addressed within each topic, with examples from different varieties of Spanish spoken in Latin America, Spain and the United States. A companion website provides additional exercises and a corpus of Spanish data for student research projects. A sample syllabus and suggestions for further reading help instructors tailor the material to a one-semester course or as a supplement to general introduction to Hispanic linguistics courses. This is an ideal resource for advanced undergraduate and postgraduate students, at level B2 - C2 of the Common European Framework for Languages, and Intermediate High - Advanced High on the ACTFL proficiency scales.